SymPy: symbolic computing in Python - Aaron Meurer; Christopher P. Smith; Mateusz Paprocki; Ondřej Čertík; Sergey B. Kirpichev; Matthew Rocklin; AMiT Kumar; Sergiu Ivanov; Jason K. Moore; Sartaj Singh; Thilina Rathnayake; Sean Vig; et al. (PeerJ Computer Science, 2017)
SymPy is an open source computer algebra system written in pure Python. It is built with a focus on extensibility and ease of use, through both interactive and programmatic applications. These characteristics have led SymPy to become a popular symbolic library for the scientific Python ecosystem. This paper presents the architecture of SymPy, a description of its features, and a discussion of select submodules. The supplementary material provide additional examples and further outline details of the architecture and features of SymPy.